Category Shift of Noun Phrases in Paula Hawkins' The Girl on the Train - Maretha, Sheila Harviana; Sumiati, Ati (Lililacs Journal, 2022)
Many languages are spoken all over the world. Each language has its own systems and characteristics. People could translate foreign languages into their languages to reduce the barrier in communication. Unfortunately, there are times when the translator has difficulty translating the source language into the target language. In consequence, a translation shift is required. This study aims to find out the dominant category shift of noun phrases in the English-Bahasa Indonesia The Girl on the Train novel. The research method adopts in this study is a descriptive qualitative method. There are two sources of data for this study: English and Bahasa Indonesia versions of The Girl on the Train. The data used are in the form of noun phrases. The data is analysed by Catford’s translation shift theory. The result of this study is all types of category shift occur: structure shift, class shift, unit shift, and intra-system shift. The most dominant category shift is structure shift (56%). Followed by intra-system shift (18%) and unit shifts (17%). And the least is class shift (9%).